EFFECTS OF TRACE METALS AND MEDIUM COMPOSITION ON THE GROWTH OF Aspergillus niger ATCC 11414, IN A SUBMERGED CULTURE - Milono Poesponegoro; Oei Ban Liang (Jurnal Kimia Terapan Indonesia, 1993)
In an attempt to optimize citric acid fermentation, a study has been conducted to determine optimum nutritional conditions for the growth of Aspergillus niger ATCC 11414. The objective of the study was to obtain information on the growth of this strain in a submerged culture for the study of citric acid production The following article summarizes the results of study on the effects of trace metals and composition of chemically defined medium on mycelial growth of A.niger ATCC 11414. Chemically defined media containing glucose as the carbon source and energy were used throughout the work. Growth experiments were carried. Out by a submerged culture process, in a 300-ml Erlenmeyer flask which contained 50ml liquid medium. The process was conducted at 30°C for 4 days in an orbital shaker incubator operated at 200 rpm. The cultivation process was followed by monitoring the changes in the culture medium of the concentrations of biomass, total reducing sugars, citric acid, and pH of the medium. It was concluded that copper (II), iron (II), zinc (II), and manganese (II) ions had a remarkable effect on the growth of A. niger ATCC 11414. With 5% glucose, the study showed that 5 - 15 ppm copper, 0.5 - 25 ppm iron and 0.5 - 25 ppb manganese ions were optimal for the growth of the strain. The growth of the strain increased with the increase of Zn2+ added (0.5 - 25 ppm). The most optimal medium for the growth of A.niger ATCC 11414 was found to be able to produce more than 16 g of dry weight of biomass for 50 g glucose.